The Global Wastewater Resistome Within a One Health Framework: Drivers, Transmission Pathways, and Public Health Implications - Taha Menasria; Nawel Zaatout (Water, 2026)
The global dissemination of antimicrobial resistance (AMR) poses a serious threat to public health, with wastewater increasingly recognized as an important reservoir and a dissemination interface for antibiotic-resistant bacteria (ARB), antibiotic resistance genes (ARGs), and mobile genetic elements (MGEs). Within the One Health framework, wastewater integrates human, animal, industrial, and environmental inputs, creating conditions that promote the selection, persistence, and dissemination of resistance determinants across interconnected ecosystems. Current advances in understanding the global wastewater resistome are reviewed, with particular emphasis on the ecological and anthropogenic drivers shaping its composition and dynamics, including antibiotic residues, co-selective contaminants, microbial community interactions, horizontal gene transfer (HGT), and wastewater treatment processes. The integration of wastewater-based genomic surveillance with epidemiological data and treatment processes is further examined to characterize resistance transmission across environmental, animal, and human interfaces. In addition, recent developments in molecular surveillance, including metagenomics and high-throughput sequencing, are critically assessed with emphasis on methodological harmonization, global monitoring disparities, and the need for standardized benchmarking frameworks to facilitate meaningful comparisons across regions. The review highlights current limitations in linking wastewater resistome profiles with clinical infection trends and discusses strategies for integrating environmental, genomic, and epidemiological data to improve and strengthen risk assessment and support the development of early-warning systems. Particular attention is given to the challenges of translating wastewater resistome data into actionable public health indicators and outlining future priorities for standardized surveillance, quantitative risk assessment, and integrated One Health mitigation strategies.